Additional L-carnitine in the gestating sow diet improves carcass characteristics of the offspring - R E Musser; Duane L Davis; K Q Owen; R E Campbell; S Hanni; J S Bauman; M Heintz; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
A total of 232 sows was used to determine the effects of an additional 50 ppm of L-carnitine in the gestation diet on sow and offspring performance. No differences were observed in either the immediate or subsequent number of pigs born or born alive per litter (P>.l 0). No differences were observed in pig weight at birth, weaning, or d 60 of age. Muscle fiber analysis of newborn pigs indicated a tendency for a larger cross-sectional area of the semitendinosus muscle; increased primary (slow-twitch, red) fibers; and a higher ratio of primary to secondary fibers (fast-twitch, white). No differences were observed in the hot carcass weight, but loin depth and percentage lean were increased in offspring ofsows fed L-carnitine during gestation. Therefore, although feeding L-carnitine during gestation had no effect on the number of pigs born, it improved carcass leanness of the offspring consistent with changes in muscle fiber characteristics. More research is needed to determine the optimum level of L-carnitine to use in the gestation diet.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; L-carnitine; Gestation; Muscle development